Niektóre dylematy dotyczące rocznego sprawozdania finansowego - Fałowski, Władysław (Some Dilemmas Concerning Annual Financial Statement, 2007)
The article discusses some chosen problems of annual financial statement such as: which information should be revealed in a financial statement, what details should a financial statement represent, which informations in a financial statement are important and useful for the economic environment? These are some crucial questions, important for an enterprise especially in the context of economy competition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 43-47